A missionary nation: race, religion, and Spain's age of liberal imperialism, 1841-1881 - Eastman, Scott (University of Nebraska Press, 2021)
"The war of Africa has been the dream of my entire political life" -- They "were calling us their liberators": the taking of Tetuán -- The visual culture of mid-nineteenth-century Spanish imperialism -- Order, progress, and civilization -- Anatomy of an uprising: race war in Santo Domingo -- Death to Spain! -- The traveling society of La Exploradora.